Necrotizing Ulcer After BCG Vaccination in a Girl With Leukocyte-adhesion Deficiency Type 1. Issue 1 (January 2018) - Kurosawa, Hidemitsu; Mizukami, Tomoyuki; Nunoi, Hiroyuki; Kato, Masaya; Sato, Yuya; Okuya, Mayuko; Fukushima, Keitaro; Katsuyama, Yoshihiko; Arisaka, Osamu
Abstract : Leukocyte-adhesion deficiency-1 is a recessively inherited disorder associated with recurrent bacterial infections, severe periodontitis, peripheral leukocytosis, and impaired wound healing. We diagnosed moderate-type leukocyte-adhesion deficiency-1 in a 7-year-old girl who developed a necrotizing ulcer after Bacillus Calmette-Guerin vaccination. The patient showed moderate expression of CD18 in neutrophils with a homozygous splice mutation with c.41_c.58+2dup20 of ITGB2 and experienced recurrent severe infections complicated with systemic lupus erythematosus. She received hematopoietic stem cell transplantation from a matched elder brother with heterozygous mutation of ITGB2, and has since remained free of infection and systemic lupus erythematosus symptoms without immunosuppression therapy.